An eccentric rod-like linear connection of two heterocycles: synthesis of pyridine trans-tetrafluoro-λ6-sulfanyl triazoles. Issue 22 (23rd May 2018) - Das, Prajwalita; Niina, Kiyoteru; Hiromura, Tomoya; Tokunaga, Etsuko; Saito, Norimichi; Shibata, Norio
Abstract : An eccentric trans -SF4 unit achieves a rod-like linear connection of two independent N-heterocycles, pyridines and triazoles. Abstract : The trans -tetrafluoro-λ 6 -sulfane (SF4 ) group has been utilized as a unique three-dimensional building block for the linear connection of two independent N-heterocycles, pyridines and triazoles. The linearly connected heterocyclic compounds were synthesized by thermal Huisgen 1, 3-dipolar cycloaddition between previously unknown pyridine SF4 -alkynes and readily available azides, providing a series of rod-like SF4 -connected N-heterocycles in good to excellent yields. X-ray crystallographic analysis of the target products revealed the trans -geometry of the SF4 group, which linearly connects two independent N-heterocycles. This research will open the field of chemistry of SF4 -connected heterocyclic compounds.